2018
DOI: 10.2478/alife-2018-0092
|View full text |Cite
|
Sign up to set email alerts
|

Farinograph Vs. Alveograph in Predictive Modelling of Wheat Flours Quality

Abstract: The aim of the research was to determine to what extent the farinograph and alveograph parameters correlate with each other, and with the physical-chemical parameters, frequently used in the evaluation of wheat flours quality. Thus, 81 samples of wheat flours were analyzed. We found a better correlation of alveographic parameters, such as Extensibility and Mechanical Work (r2 varied between 0.48-0.51), with Protein content and Gluten content of flours, compared to farinographic parameters: Development time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…According to the Chaddock's scale for evaluation of correlation strength (Žižić et al, 1999), the observed relations between FWA and content of chemical compounds are strong. These findings are in compliance with Tamba-Berehoiu et al (2018) research, where a significant positive correlation has been found between FWA and protein content.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to the Chaddock's scale for evaluation of correlation strength (Žižić et al, 1999), the observed relations between FWA and content of chemical compounds are strong. These findings are in compliance with Tamba-Berehoiu et al (2018) research, where a significant positive correlation has been found between FWA and protein content.…”
Section: Resultssupporting
confidence: 92%
“…Correlation between DDT and protein content, starch content, farinograph water absorption, quality number and overall sensory quality of bread is positive, but for water content and SD it is negative. According to Tamba-Berehoiu et al (2018) study there is a very significant and positive correlation between DDT and protein content, which is in compliance with our research.…”
Section: Resultssupporting
confidence: 91%
“…Similar research work as above regarding sensory attributes had been conducted for evaluating sensory and textural properties of chapatti [23]. Significant correlation of wet and dry gluten was recorded with water absorption and dough stability during study on quality of wheat flour [24]. In a study significant correlation was determined between dough development and dough stability time; whereas mixing tolerance index indicated significantly negative correlation [25].…”
Section: Physicochemical Propertiesmentioning
confidence: 66%
“…A study reflected significant correlation between alveographic parameters and sensory characteristics of intended product made by wheat flour containing small portion of rice bran [29]. Another study on wheat flour quality reflected significant correlation between P − P/L, W-L, W-Wabs, P/L-P and L [30].…”
Section: Rheological Parametersmentioning
confidence: 96%